Social capital in science-technology and its components - Giang, Nguyen Huong (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT)
Social capital in Science and Technology (S&T) and its components are new and important topics which need to be studied exhaustively in order to get solutions for enhancing and developing this capital source. One of its components is S&T communication which has played an important role for S&T development of the country. Code: 13042301